Inovasi Digital dalam Pemerintahan: Pengaruh SICARAM terhadap Kinerja Perangkat Daerah - Anggraini, Nur; Putra, Raniasa; Hidayat, Bachtari Alam (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
One of the innovations developed by the Ogan Ilir Regency Government is the Information System for Monitoring Development Achievement (SICARAM), aimed at facilitating the monitoring and evaluation of planned development outcomes. This study aims to analyze the influence of SICARAM implementation on the performance of local government agencies. The research employed a descriptive quantitative approach, with SICARAM implementation as the independent variable (X) and organizational performance as the dependent variable (Y). The sample consisted of 60 respondents selected using the total sampling method. Data were collected through a Likert-scale questionnaire (1–4) comprising 16 items, which were tested for validity and reliability. The data were analyzed using multiple linear regression with SPSS 25. The results showed that SICARAM implementation has a positive and significant effect on the performance of local government agencies in Ogan Ilir Regency. Although the implementation of SICARAM has been relatively effective, improvements in communication and bureaucratic structure are still needed. The performance of local agencies is generally adequate; however, aspects such as work quantity and timeliness require enhancement. This study recommends strengthening training efforts and simplifying bureaucratic procedures, and suggests further research to explore individual factors such as digital literacy and work motivation in the use of local information systems.